Whiteness in Latin America: measurement and meaning in national censuses (1850-1950) - Mara Loveman (Journal de la Société des Américanistes)
Whiteness in Latin America: measurement and meaning in national censuses (1850-1950). Drawing on an analysis of all national censuses conducted in Latin America from 1850 to 1950, this article examines how tacit assumptions about the nature of « whiteness » informed the production of statistical knowledge about Latin American populations. For insight into implicit racial beliefs that shaped census-taking in this period, the article considers how census agents accomplished three basic tasks: 1) identifying the « race » of individuals in the population; 2) preparing statistical tables to publicize census results; and, 3) projecting the racial composition of national populations in the future. The analysis identifies variation in notions of « whiteness » across the region, but also points to a set of broadly shared premises about the nature, value, and boundaries of whiteness that transcended nation-state boundaries in this period. Fundamental similarities in ideas about whiteness found in Latin American censuses appear even more starkly when the scope of analysis expands to include the censuses of the United States.